Beyond the schoolhouse gate : free speech and the inculcation of values - Lane, Robert Wheeler, 1954- (Temple University Press, 1995)
Outstanding Academic Title, Choice, 1995 "What makes Lane's approach unique is that he weaves together different perspectives on the nature of school into a very colorful but informative and lucid tapestry that seeks the outer limits of free expression within the boundaries of the school context, always with an eye toward promoting the goal of inculcation of values, a worthy end for students and school officials alike." a"Samuel M. Davis, Allen Post Professor of Law, University of Georgia *In a 1969 landmark case, the U.S. Supreme Court ruled that the suspension of student for protes.